PERANCANGAN DAN SOSIALISASI SISTEM PENGAMAN INSTALASI LISTRIK PADA GEDUNG FASILITAS UMUM DI DESA PEKUTATAN JEMBRANA BALI - Wijaya, I.W.A; Janardana, I.G.N; Partha, C.G.I.; Budiastra, I.N.; Swamardika, I.B.A.; Sukerayasa, I.W. (Buletin Udayana Mengabdi; Vol 17 No 1 (2018): Buletin Udayana MengabdiDO - 10.24843/BUM.2018.v17.i01.p03, 2018)
design of electricity power installation, there are some items that have to be focused, one of them is the security system design. In security system, accurate calculation is highly required to avoid dangers caused by the usage of electricity power. One public facility that will be built in Pekutatan village is Wantilan. In Wantilan, all villagers’ activities can be done. To support these activities, electricity installation must be installed. In order to correctly use the electricity, a design of security system is required to prevent dangers caused by electricity failures. In designing electricity installation for Wantilan, it must refer to the PUIL 2011. To answer the above issue, a public service to the villagers of Pekutatan village has been done. The public service is composed by security system design, electricity power installation, security panel installation, and providing a tutorial about the danger of electricity and how to correctly use electricity energy.